2016
DOI: 10.1161/circoutcomes.115.002461
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cognition and Brain Atrophy Decades After Hypertensive Pregnancy Disorders

Abstract: Background Hypertensive pregnancy disorders have been associated with subjective cognitive complaints or brain white matter lesions five to ten years after the hypertensive pregnancy. The long-term effects of hypertensive pregnancies on brain structure and cognitive function remain unknown. Methods and Results This study included 1279 women who participated in the Family Blood Pressure Project Genetic Epidemiology Network of Arteriopathy (GENOA) study. As part of the ancillary Genetics of Microangiopathic Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 35 publications
3
65
5
Order By: Relevance
“…Women in the PE group had significantly smaller brain volumes, with corresponding increases in lateral ventricular volumes. A recent study involving a large multiethnic and racially diverse sample observed that women with a history of hypertensive pregnancy had smaller brain volumes and larger degrees of atrophy decades after the index pregnancy (229). While not a sole indicator of neurological dysfunction, these alterations in brain size and volume are accompanied by changes in cerebral hemodynamics, electrophysiology, cognition, and behavior in human PE patients.…”
Section: Cerebrovascular and Higher Function Neurological Consequencementioning
confidence: 99%
See 2 more Smart Citations
“…Women in the PE group had significantly smaller brain volumes, with corresponding increases in lateral ventricular volumes. A recent study involving a large multiethnic and racially diverse sample observed that women with a history of hypertensive pregnancy had smaller brain volumes and larger degrees of atrophy decades after the index pregnancy (229). While not a sole indicator of neurological dysfunction, these alterations in brain size and volume are accompanied by changes in cerebral hemodynamics, electrophysiology, cognition, and behavior in human PE patients.…”
Section: Cerebrovascular and Higher Function Neurological Consequencementioning
confidence: 99%
“…Diagnostic imaging reveals that these WMLs can persist for years after the index pregnancy (2224, 229). Counterintuitively, the pattern of distribution of WMLs associated with preeclampsia differs from that of Posterior Reversible Encephalopathy Syndrome (PRES).…”
Section: Cerebrovascular and Higher Function Neurological Consequencementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that hypertensive pregnancy disorders have an increased, sex-specific risk of cognitive decline and dementia among women 5 to 10 years after the hypertensive pregnancy (Aukes et al 2007;Postma et al 2014a;. Moreover, a recent study has shown that hypertensive pregnancy disorders are associated with worse performance in tests of processing speed and smaller brain volumes decades later, when compared with women with histories of normotensive pregnancies (Mielke et al 2016). Other studies have demonstrated that stress during pregnancy durably hampers maternal body-weight growth, increases anxiety-like behaviors, and affects reactivity to stress in mothers more than 1 month after the stress exposure (Darnaudéry et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These data imply a long-term, significant impact of adverse pregnancy on behaviors in mothers. Given normal reproduction experience and the adverse gestational conditions mentioned above can chronically affect cognitive functioning or other behaviors (Li et al 2013;Mielke et al 2016;Darnaudéry et al 2004), so it is plausible to hypothesize that gestational inflammation can impact the AAMI and corresponding neural substrates in the mother-self during aging.…”
Section: Introductionmentioning
confidence: 99%